2017
DOI: 10.1016/j.intermet.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Deformation characteristics of the intermetallic alloy 60NiTi

Abstract: The deformation behavior of a Ni-rich Ni 55 Ti 45 (at.%) alloy, commonly known as 60NiTi (as designated in wt.%), was analyzed using neutron and synchrotron x-ray diffraction during in situ isothermal tension and compression loading, and pre and post-test electron microscopy. The alloy is shown to exhibit remarkable strength and high hardness resulting from a high density of fine Ni 4 Ti 3 precipitates (size ~67 nm), which were uniformly dispersed throughout the matrix after a solution treatment and oil quench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…The obtained results correspond to the literature, [18][19][20] where the authors determined that the brittleness of the as-cast NiTi alloy is mainly influenced by the high cooling rate of the alloy and its higher nickel content. If the as-cast NiTi alloy is furnace cooled or later hot worked, it also shows ductile properties.…”
Section: Tensile Testsupporting
confidence: 88%
See 1 more Smart Citation
“…The obtained results correspond to the literature, [18][19][20] where the authors determined that the brittleness of the as-cast NiTi alloy is mainly influenced by the high cooling rate of the alloy and its higher nickel content. If the as-cast NiTi alloy is furnace cooled or later hot worked, it also shows ductile properties.…”
Section: Tensile Testsupporting
confidence: 88%
“…Also higher Ni content means higher hardness. 19 From this it can be concluded that over 550 HV hardness of CVC NiTi rod is comprehensible due to its high Ni content (x Ni = 60 %) and fast water cooling during drawing.…”
Section: Hardnessmentioning
confidence: 83%
“…Ni4Ti3 precipitates were not observed in this sample. [42], and can also become the sources for fatigue failure, wear failure, and localized corrosion [43].…”
Section: Solution Annealing and Aging At 550 ºC For 4 Hmentioning
confidence: 99%
“…Highly Ni-rich NiTi alloys (>52 at%) have an advantageous set of properties needed for structural application [17]. Among the highly Ni-rich NiTi alloys, one that has recently received wide interest is 60NiTi (60 wt% Ni) bulk alloy [17−28].…”
Section: Introductionmentioning
confidence: 99%